A Qualitative Analysis of Family Dynamics and Motivation in Sessions With 15 Women in Drug Treatment Court. (January 2019) - Goldberg, Zoe E; Chin, Nancy P; Alio, Amina; Williams, Geoffrey; Morse, Diane S
Women with substance use disorders (SUDs) often experience inadequate health care, mental and physical health problems, trauma, lack of social support, and undermining of support for psychological needs of autonomy, competence, and relatedness needed for motivation and well-being. For women with SUD trying to reclaim sobriety and a healthy life, family can present both barriers and support. The aim of this study is to gain a deeper understanding of the intersection of family relationships with motivation of women in Drug Treatment Court (DTC) to attain their health goals. Data consist of transcribed intervention sessions between trained peer interventionists and 15 DTC participants from The Women's Initiative Supporting Health DTC Intervention Study. This analysis uses a qualitative framework approach to analyze the data. The Self-determination Theory of human motivation and Family Systems Theory provide the conceptual framework to understand how participants' expressions of motivation-related basic needs of autonomy, competence, and relatedness and change-related behaviors interfaced with family support. Analysis revealed more mentions of family in motivation-supportive contexts than in motivation-thwarting contexts, but highlighted complex roles families can play in health of women in recovery from SUD. Providers may be able to incorporate this knowledge to address the needs of this challenging population.